Pengaruh Pembelajaran Berbasis STEAM Terhadap Kreativitas dan Hasil Belajar Peserta Didik di Homeschooling Pena Surabaya - Umma, Farah Khosravi; Riyanto, Yatim (J+PLUS UNESA, 2023)
The 21st century, the era of the industrial revolution 4.0, had significant consequences for education, especially in the learning process in the classroom. Learning innovation in the industrial revolution 4.0 era is important for renewal of learning that is able to answer the challenges of digital technology development. The National Education Association identifies 21st century skills as the "4 C's". The "4Cs" cover critical thinking, creativity, communication and collaboration. Four skills that education must achieve in the 21st century. One of them is creativity, an important skill achieved by students in the industrial era 4.0. This study uses quantitative research, a type of pre-experimental research that uses a One-Shot case study and One Group pretest-posttest. The effect of STEAM learning on student creativity is 69.25%, meaning that the percentage criteria show high results, and the effect of STEAM learning on student learning outcomes from the pre-test and post-test results there is a significant difference between pre-test and post-test namely 63.89% and 81.67%.